2022
DOI: 10.1113/ep090326
|View full text |Cite
|
Sign up to set email alerts
|

Blunted hypoxic pulmonary vasoconstriction in apnoea divers

Abstract: Competitive apnoea divers dive repetitively to depths >50 m. During the final portions of ascent, divers experience significant hypoxaemia. Additionally, hyperbaria during diving increases thoracic blood volume while simultaneously reducing lung volume and increasing pulmonary artery pressure. We hypothesized that divers would have exaggerated hypoxic pulmonary vasoconstriction, leading to increased right heart work owing to their repetitive hypoxaemia and hyperbaria, and that the administration of sildenafil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 92 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…There is a renewed interest in the mechanisms and (mal)adaptability of HPV in humans, highlighted in recent publications focused on static apnoea and high-altitude acclimatization (Jernigan et al, 2021;Kelly et al, 2022;Subedi et al, 2022). These studies have confirmed the modulatory significance of iron on HPV, providing clues to the limits of physiological adaptation to terrestrial extremes that have translational relevance for mechanisms of disease.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…There is a renewed interest in the mechanisms and (mal)adaptability of HPV in humans, highlighted in recent publications focused on static apnoea and high-altitude acclimatization (Jernigan et al, 2021;Kelly et al, 2022;Subedi et al, 2022). These studies have confirmed the modulatory significance of iron on HPV, providing clues to the limits of physiological adaptation to terrestrial extremes that have translational relevance for mechanisms of disease.…”
mentioning
confidence: 97%
“…HPV also plays important roles postnatally in relationship to several extreme physiological and clinical phenomena, helping to restore the matching of pulmonary perfusion to ventilation when hypoxic regions in the lung develop. There is a renewed interest in the mechanisms and (mal)adaptability of HPV in humans, highlighted in recent publications focused on static apnoea and high‐altitude acclimatization (Jernigan et al., 2021 ; Kelly et al., 2022 ; Subedi et al., 2022 ). These studies have confirmed the modulatory significance of iron on HPV, providing clues to the limits of physiological adaptation to terrestrial extremes that have translational relevance for mechanisms of disease.…”
mentioning
confidence: 99%